Predictive value of T2-FLAIR signal suppression rate for 1p/19q molecular features in lower-grade gliomas - WANG Hanwei; ZENG Linlan; ZHAO Mimi (陆军军医大学学报, 2024)
Objective To evaluate the predictive value of T2-fluid attenuated inversion recovery (FLAIR) signal suppression rate for the short arm of chromosome 1 and long arm of chromosome 19 (1p/19q) molecular features in lower-grade gliomas (LGG), and to construct and verify the predictive model based on magnetic resonance imaging (MRI) tumor features and T2-FLAIR signal suppression rate. Methods Clincal and imaging data of the patients with pathologically confirmed supratentorial LGG (WHO grade 2~3) in our medical center from 2017 to 2021 were collected and retrospectively analyzed. According to the results of postoperative molecular pathology, they were divided into 1p/19q-codeleted (1p/19q-Codel) and 1p/19q-noncodeleted (1p/19q-Noncodel) groups. MRI tumor features were blindly assessed by 2 neuroradiologists. Five circular regions of interest were respectively delineated in the tumor area and the normal-appearing white matter in contralateral semioval center using the hot-spot method in order to calculate the T2-FLAIR signal suppression rate. The differences of clinical features, MRI tumor features and T2-FLAIR signal suppression rate were analyzed between the 2 groups. Univariate and multivariate logistic regression analyses were used to screen independent predictors and constructa predictive model and nomogram. Receiver operating characteristic (ROC) curve, calibration curve and Hosmer-Lemeshow test were applied to assess the model performance, and the model was internally validated by bootstrap method. Results A total of 146 supratentorial LGG patients were enrolled, including 68 being assigned into the 1p/19q-Codel group and 78 into the 1p/19q-Noncodel group. The T2-FLAIR signal suppression rate was 0.43 (0.28, 0.62) in the 1p/19q-Noncodel group, which was significantly higher than that in the 1p/19q-Codel group [0.29 (0.24, 0.35), P<0.001]. Multivariate logistic regression analysis showed that T2-FLAIR signal suppression rate >0.374 (P<0.001), cortex infiltration (P=0.001) and calcification (P=0.004) were independent predictors for 1p/19q status. The AUC value of T2-FLAIR signal suppression rate >0.374 in predicting 1p/19q-Noncodel was 0.720, the sensitivity was 60.26% and the specificity was 83.82%. DeLong test indicated that T2-FLAIR signal suppression rate >0.374 was more effective than T2-FLAIR mismatch sign in predicting 1p/19q molecular features (P<0.001). ROC curve analysis suggested that the predictive model established by T2-FLAIR signal suppression rate >0.374 combined with cortex infiltration and calcification had good performance, with an AUC value of 0.808, and the AUC value verified internally by bootstrap method was 0.807. At the same time, the calibration and goodness of fit of the model were good. Conclusion T2-FLAIR signal suppression rate can be used as a quantitative imaging marker to predict 1p/19q-Noncodel LGG. The predictive model with T2-FLAIR signal suppression rate >0.374 combined with cortex infiltration and calcification can effectively predict 1p/19q molecular features.